Studies from the Norwegian Twin Registry on risk factors for health related work incapacity. (13th November 2019) - Orstavik, R; Seglem, K; Gjerde, L C; Torvik, F; Røysamb, E; Reichborn-Kjennerud, T; Vollrath, M
Abstract: Background: For the past decade, researchers from the Nordic countries have taken the advantage of their large twin cohorts and reliable official registries to deepen our understanding of sick leave and disability pension. This presentation will give a brief summary of studies based on data from The Norwegian Twin Registry (NTR). Methods: Monozygotic twins develop from one fertilized egg cell and are genetically identical, while dizygotic twins are the result of two fertilized egg cells and share, as ordinary siblings, in average 50% of their segregating genes. With data from large cohorts of twins reared together, it is possible to calculate the proportion of variance in an outcome that stems from genetic, shared and non-shared environmental factors respectively. Furthermore, when exploring the contribution from measured risk factors on specific outcomes, adjustment for unmeasured confounders (genes and shared environment) can bring us closer to determine causality in epidemiological studies. Both methods were applied in our studies. NTR now includes data from about 30 000 twins, but until recently we focused on a subsample of about 8 000 young adults (born 1967-1979). Data from questionnaires and interviews were linked to registries on sick leave and disability pension. Results: In line with previous studies, we found that the liability to sick leave and disability pensioning, as well as the transition from the former to the latter, was strongly to moderately influenced by genetic factors. We found no evidence for "social transmission", e.g. that environmental factors shared by the twins contributed to these outcomes. Further details and results from studies on measured risk factors, with emphasize on mental health, will be presented at the conference. Conclusions: Twin studies cast light on different aspects of work incapacity, including reducing stigma such as those associated with theories of social transmission of health related benefits.